THE INFLUENCE OF ORGANIZATIONAL CULTURE ON EMPLOYEE WORK OUTCOMES AND COMPANIES’ PERFORMANCE WITHIN THE E-COMMERCE SECTOR - Margono , Yedija Christopher William; Barry, Rinto Rain (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study aims to determine the effect of organizational culture in Indonesian e-commerce companies on work results and employee performance. This study describes satisfaction at work, productivity at work, and quality of work because of organizational culture on profitability and growth, organizational innovation. Using a sample of 230 employees from two large Indonesian e-commerce companies, we focused on full-time employees who had at least one year of professional experience and participated in this study. The questionnaire instrument in this study used a Likert scale and the data were analysed by PLS-SEM using Smart-PLS 3.0. Several conclusions can be drawn from the results of this study: Organizational Culture positively affects Satisfaction at Work, Organizational Culture positively affects Productivity at Work, Organizational Culture positively affects Quality of Work, Satisfaction at Work is not positively affected Profitability and Growth, Productivity at Work is positively affected to Profitability and Growth of the company, and Quality of Work is positively affected to Organizational Innovation.